How is flood risk explained in the subject of geography in Spanish schools? An approach based on social science textbooks (primary education) - Morote, Álvaro-Francisco; Olcina, Jorge; Hernández, María (International research in geographical and environmental education, 2023)
The main natural risk in the Mediterranean region is flooding. Therefore, in Spain, explaining this issue in Primary Education classrooms of Social Sciences should be a priority and is established as such in the current curriculum. The aims of this study are to carry out an analysis of the contents on flood risk included in the Social Science textbooks (3 rd cycle; 5 th and 6 th ) of Primary Education of the leading publishers used in Spain (Anaya, Bromera, Santillana, SM and Vicens Vives), in terms of: (1) the meaning of this phenomenon; (2) the causes and consequences of floods; and (3) an analysis of the images (catastrophism and territory location) that are included in the textbooks to explain these events. The results indicate that there is no complete definition of flood risk provided in these textbooks; the information is mainly related to the physical factor (atmospheric event). There is no specific mention of how human beings affect risk (vulnerability and exposure factor). With respect to the causes of floods, the analysis finds confusion in the explanations from the different textbooks and publishers, and the images that are included are sensationalist, highlighting the catastrophism without indicating to which territory it refers.